2007
DOI: 10.3354/dao074001
|View full text |Cite
|
Sign up to set email alerts
|

Fate of infectious salmon anaemia virus (ISAV) in experimentally challenged blue mussels Mytilus edulis

Abstract: In order to investigate the potential role of blue mussels Mytilus edulis as a vector of the fish pathogenic infectious salmon anaemia virus (ISAV), we developed an experimental bioaccumulation system in which mussels can accumulate virus during normal filtration. Detection of virus in mussels was performed by means of real-time RT-PCR. ISAV-RNA was detected in the mussels until 72 h post-challenge. Hepatopancreas homogenate from experimentally challenged mussels was injected into salmon. All the fish injected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 19 publications
2
33
0
1
Order By: Relevance
“…Organic extractive species (e.g., mussels) have also demonstrated their ability to consume parasites and inactivate pathogens. The novel use of cleaner-fish is also being trialed and has shown promise in, for example, the removal of sea-lice from Atlantic salmon [145,146,177,178]. Culturing species form different trophic levels can achieve environmental stability through the biomitigation of aquaculture wastes, while at the same time providing the farmer economic stability through product diversification [2,129].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Organic extractive species (e.g., mussels) have also demonstrated their ability to consume parasites and inactivate pathogens. The novel use of cleaner-fish is also being trialed and has shown promise in, for example, the removal of sea-lice from Atlantic salmon [145,146,177,178]. Culturing species form different trophic levels can achieve environmental stability through the biomitigation of aquaculture wastes, while at the same time providing the farmer economic stability through product diversification [2,129].…”
Section: Discussionmentioning
confidence: 99%
“…If V. anguillarum can persist in mussel fecal pellets, it is possible that mussels could generate Vibrio reservoirs in sediments and/or fecal matter [4,144]. Other studies, however, have demonstrated that bivalves are not hosts, instead consuming parasites or inactivating pathogens [145,146]. More research into bivalves' ability to act as pathogen reservoirs is required, however, steps can be taken to minimize the risk of transmission.…”
Section: Integrated Multi-trophic Aquaculture (Offshore and On-land)mentioning
confidence: 99%
See 1 more Smart Citation
“…Bivalves bioaccumulate both viral and bacterial finfish pathogens (5)(6)(7)(8)(9)(10). The physiology of the pathogen influences whether the pathogen remains viable in shellfish tissues and is shed back into the environment.…”
mentioning
confidence: 99%
“…For instance, blue mussels may have a beneficial effect in a net pen environment by reducing the amount of the kidney disease bacterium Renibacterium salmoninarum present (Paclibare et al 1994). Bivalves are also capable of retaining fish pathogenic viruses, but persistence periods vary greatly, presumably reflecting differences in the robustness of the viruses (Mortensen et al 1992, Skår & Mortensen 2007.…”
Section: Introductionmentioning
confidence: 99%